Beyond Team Types and Taxonomies: A Dimensional Scaling Conceptualization for Team Description - Hollenbeck, John R.; Beersma, Bianca; Schouten, Maartje E. (Academy of Management Review, 2012)
Research on teams has prompted the development of many alternative taxonomies but little consensus on how to differentiate team types. We show that there is greater consensus on the underlying dimensions differentiating teams than there is on how to use those dimensions to generate categorical team types. We leverage this literature to create a conceptual framework for differentiating teams that relies on a dimensional scaling approach with three underlying constructs: skill differentiation, authority differentiation, and temporal stability.